Dynamic modeling and comparative analysis of heat exchangers in supercritical CO2 power cycles - Tianyang Qin; Yuwei Sun; Wei Wei; Jie Lin; Xinping Yan (Case Studies in Thermal Engineering)
Heat exchangers are essential in supercritical CO2 power cycles, where accurate dynamic modeling is required to capture transient thermal-hydraulic behavior. This study develops a one-dimensional dynamic model of a printed circuit heat exchanger used as the system cooler, based on the finite volume method in Modelica. A sensitivity analysis indicates that 100 control volumes achieve a balance between accuracy and computation efficiency, with limited influence on system dynamics. The model was validated using experimental data from a megawatt-scale heat exchanger and three-dimensional simulations. Deviations from experimental data were under 10 %, while those from simulations were below 0.15 % in mass flow rate, temperature, and pressure, and 8.1 % in stabilization time. Simplified governing equations were evaluated. Replacing the momentum equation with a pressure drop model reduced simulation time by 78.2 %, from 411 to 89.3 s. Incorporating wall heat transfer based on thermal conductivity improved accuracy with only a 5-s increase in computation time. Omitting this effect caused a temperature deviation of about 3 K at the CO2 outlet. This study confirms the effectiveness of one-dimensional models for heat exchanger dynamic analysis, offering insights into heat exchanger modeling for dynamic analysis in supercritical CO2 power cycles.